SN 2024abfo: A partially stripped type II supernova from a yellow supergiant - Reguitti, A.; Pastorello, A.; Smartt, S. J.; Valerin, G.; Pignata, G.; Campana, S.; Chen, T. -W; Sankar, A. K.; Moran, S.; Mazzali, P. A.; Duarte, J.; Salmaso, I.; et al. (EDP Sciences, 2025)
We present photometric and spectroscopic data of the type IIb supernova (SN) 2024abfo in NGC 1493 (at 11 Mpc). The steroid Terrestrial-impact Last Alert System (ATLAS) survey discovered the object just a few hours after the explosion and observed a fast rise on the first day. Signs of the sharp shock breakout peak and the subsequent cooling phase are observed in the ultraviolet and the bluest optical bands in the first couple of days, while no peak is visible in the reddest filters. Subsequently, in analogy with normal SNe IIb, the light curve of SN 2024abfo rises again in all bands to the broad peak, with the maximum light reached around 1 month after the explosion. Its absolute magnitude at peak is M-r = -16.5 +/- 0.1 mag, making it a faint SN IIb. The early spectra are dominated by Balmer lines with broad P Cygni profiles, indicating ejecta velocity of 22 500 km s(-1). One month after the explosion, the spectra display a transition towards being He-dominated, though the H lines do not completely disappear, supporting the classification of SN 2024abfo as a relatively H-rich SN IIb. We identify the progenitor of SN 2024abfo in archival images of the Hubble Space Telescope, the Dark Energy Survey, and the XMM-Newton space telescope, in multiple optical filters. From its spectral energy distribution, the progenitor is consistent with being a yellow supergiant, having an initial mass of 15 M-circle dot. This detection supports an emerging trend of SN IIb progenitors being more luminous and hotter than SN II ones, and being primaries of massive binaries. Within the SN IIb class, fainter events such as SN 2024abfo tend to have cooler and more expanded progenitors than luminous SNe IIb.